Transportation asset management for local government agencies : threshold levels and best practice guide - Bernardin, Vincent Jr.; Durango-Cohen, Pablo; Czepiel, Edward (Midwest Regional University Transportation Center, 2006)
The Federal Highway Administration defines transportation asset management as "a systematic process of operating, maintaining, and upgrading infrastructure cost-effectively." The objective of this report is to help county and municipal-level agencies implement transportation asset management techniques. The report represents a synthesis of the current literature on asset management relevant to local governments as well as a significant contribution to the subject. The report represents an important reference and resource for local government agencies and functions as a synthesis by (1) reviewing and re-presenting the concepts, strategies and tools of asset management, (2) identifying other important transportation asset management references and resources for local agencies, and (3) documenting the successful implementation of asset management techniques by local governments. The report makes important new contributions to the field by (4) identifying strategies, such as coordinated maintenance and group purchasing, particularly important for asset management at the local level, (5) reviewing commercially available software tools, (6) recommending standards of practice for agencies of various sizes, and (7) identifying future work important to advancing the state of the practice of asset management at the local government level. The report was based upon an extensive review of both the academic and professional literature, including online/web resources; a review and metaanalysis of surveys of local agencies on the topic of transportation asset management supplemented by a new, limited survey; a survey of software vendors providing asset management software to county and municipal governments; and the input of practitioners and experts in the field.
125 p.
Keywords: Asset management; Best practices; City government; County government; Local government agencies